Data‐bility: Endogamous social intimacies on dating apps in Mumbai - Dattani, Kavita (Transactions - Institute of British Geographers (1965), 2025)
In this paper I argue through the double entendre of ‘data‐bility’ that how dateable one is on a dating app relies on data. This techno‐social framework enables an understanding of how dating apps are reconfiguring a politics of sexuality, circumscribed by digital technologies and data. Drawing on research with middle‐class women and gender‐minority dating app users in Mumbai and one dating app executive, the paper investigates how algorithms and users' digital behaviour together constitute data‐bility in three ways. First, dating app algorithms are designed to match those of similar social identities to one another. Second, dating app users engage with others' digital data on profiles and through message chats, reading class through these processes, deciding who to match/reject and correspondingly who is data‐ble. Third, users and algorithmic infrastructures come together to create new regimes of verification, through deeming some users ‘real’ and others ‘fake’ on dating apps, extending violent legacies of categorisation. Together, these processes result in data‐bility, a techno‐social order of digital dating oriented around the exclusion of those labelled ‘creeps’ along class and caste lines. Short In this paper I draw on research with middle‐class women and gender‐minority dating app users in Mumbai and one dating app executive to argue, through the double entendre of ‘data‐bility’, that how dateable one is on a dating app relies on data. This techno‐social framework enables us to understand how dating apps are reconfiguring a politics of sexuality in India, circumscribed by digital technologies and data.